PERAN PESANTREN MODERN DALAM MENJAWAB TANTANGAN MODERASI BERAGAMA SAAT INI - Dewi, Hardianti Putri; Yusri, Mustami; Ridani, Ridani (STAI Darul Qalam Tangerang, 2023)
The main objective of this research is explore the crucial role that modern pesantren plays in addressing the challenges related to religious moderation. Additionally, this study aims to highlight how modern pesantren can contribute positively to the promotion of religious moderation and strengthening tolerance among followers of different religions. By becoming a hub for moderate religious education and understanding, modern pesantren can guide individuals on simplicity, diversity, and peace within their religion. The integration of social, economic, and political aspects in the education provided by modern pesantren can also help students develop an appreciation for tolerance and respect for differences, leading to a more harmonious society. Modern pesantren can also nurture critical and moderate values among students, thereby creating a quality young generation that can make positive contributions to society. Collaboration between modern pesantren and other organizations, such as the government and civil society, can enhance awareness of the significance of harmony and tolerance among followers of different religions. In summary, modern pesantren plays a crucial role in tackling the challenges of religious moderation and can foster a tolerant and reconciled society through its emphasis on moderate and holistic religious learning and collaboration with others